Gastrointestinal involvement in the Ehlers–Danlos syndromes. Issue 1 (10th February 2017) - Fikree, Asma; Chelimsky, Gisela; Collins, Heidi; Kovacic, Katcha; Aziz, Qasim
Abstract : Current evidence suggests that an association exists between non‐inflammatory hereditary disorders of connective tissue such as the Ehlers–Danlos syndromes (EDS) and gastrointestinal (GI) symptoms. Patients with EDS can present with both structural problems such as hiatus hernias, visceroptosis, rectoceles, and rectal prolapse as well as functional problems such as disordered gut motility. It has recently been demonstrated that patients with hypermobile EDS (hEDS) present with GI symptoms related to the fore and hind‐gut and these patients frequently meet the criteria for functional gastrointestinal disorders such as functional dyspepsia and irritable bowel syndrome. Presence of GI symptoms in EDS patients influences their quality of life. Specific evidence based management guidelines for the management of GI symptoms in EDS patients do not exist and these patients are often treated symptomatically. There is, however, recognition that certain precautions need to be taken for those patients undergoing surgical treatment. Future studies are required to identify the mechanisms that lead to GI symptoms in patients with EDS and more specific treatment guidelines are required. © 2017 Wiley Periodicals, Inc.